Mobilising knowledge to improve UK health care: learning from other countries and other sectors - a multimethod mapping study - Huw TO Davies; Alison E Powell; Sandra M Nutley (National Institute for Health Research, 2015)
Background: The past two decades have seen rich conceptual development and a wide variety of practical initiatives around research use or 'knowledge mobilisation', but so far there has been little systematic effort to map, conceptualise and learn from these initiatives, or to investigate the degree to which they are underpinned by contemporary thinking as set out in the literature. This gap is particularly apparent when looking at knowledge mobilisation at the 'macro' level, that is the strategies and activities of major research funders, major research producers and key research 'intermediaries'. Aims and objectives: The study had three key objectives with associated research questions: to map the knowledge mobilisation landscape in health care (in the UK and internationally) and in social care and education within the UK; to understand the models, theories and frameworks that underpin the approaches to knowledge mobilisation; and to learn from the success or otherwise of the strategies and approaches in use. Methods: The study was multimethod and multiphased, with considerable interactivity between the different strands. Data were collected through a review of 71 published reviews on knowledge mobilisation; website review of the knowledge mobilisation activities of 186 agencies; in-depth interviews (n = 52) with key individuals in agencies; a web survey (response rate 57%; n = 106); and two stakeholder workshops (at months 6 and 16). Findings: We identified a wide range of models, theories and frameworks used to describe knowledge mobilisation and created a conceptual map that highlights six domains of thinking and debate in the literature. The interview and survey data showed three broad, overlapping roles undertaken by agencies: developing and sharing research-based products; emphasising brokering; and focusing on implementation. The knowledge mobilisation approaches in use had been shaped by many factors but there was only limited use of the models, theories and frameworks from the literature. Participants saw formal evaluation of knowledge mobilisation activities as important but highly challenging. Rich formative experience was described but formal evaluation was relatively rare. Few agencies involved service users or members of the public in knowledge mobilisation activities. Working inductively from the study data we derived eight key archetypes or 'bundles of knowledge mobilisation activities' that could be used by agencies to explore their knowledge mobilisation activities, future strategies and stakeholder perspectives. Conclusions: Knowledge mobilisation could be enhanced by providing support to enable cross-sector and interagency learning, reflection on the conceptual basis of approaches and increased evaluation of knowledge mobilisation activities. Further research is needed to evaluate approaches to assessing research use and impact, on systems approaches to knowledge mobilisation, on sustaining and scaling-up approaches, and on applying a wider range of literatures to knowledge mobilisation. Further research would also be useful on the knowledge mobilisation archetypes and how they can work in complementary ways. Funding: The National Institute for Health Research Health Services and Delivery Research programme.